The 2:3:6 quasi-periodic oscillation structure in GRS 1915+105 and cubic subharmonics in the context of relativistic discoseismology - Ortega Rodríguez, Manuel (2014)
Artículo científico -- Universidad de Costa Rica, Cenrtro de Investigaciones Geofísicas. 2013